O Movimento Escola Sem Partido, e suas implicações para a Educação Pública no Paraná: a posição das câmaras municipais - Barbosa, Débora Silva (2023)
The research that was carried out addresses the theme Apolitical schools, a movement created by Miguel Nagib, attorney for the State of São Paulo, whose objective, according to its creator, was to prove that there was indoctrination in schools committed by teachers, who were accused of spreading leftist ideas and which confront the values of Brazil's ruling and conservative class. The movement took place through a website, which served to host videos of teachers teaching classes, photos of activities, testimonials from students and parents of students, and articles by people from the liberal sector that would serve to support the fight against supposed indoctrination. At first, the movement did not show significant support, but that changed at the end of the first term of former President Dilma Rousseff, and intensified with her re-election, becoming the subject of debates in universities, unions, in the media, social networks and even even in elections. This research aims to analyze the Apolitical schools movement at its core, having the State of Paraná as a locus, in which it sought to research in the 399 municipalities, in which city councils the proposals that sought to institute the Apolitical schools in their legislatures. For the elaboration of the dissertation, bibliographical research was used, focusing on Marilena Chauí, Luiz Antônio Cunha, Louis Althusser and Karl Marx regarding the concept of ideology, and Gaudêncio Frigotto, who dedicated several works to the theme of Apolitical schools. In addition to reading other authors who deal with the subject addressed here, in articles, books and other postgraduate research, a search was carried out on the websites of all municipalities in Paraná, through the search feature for Legislative Matters on the websites themselves, or, in rare cases, through a broader search for news through the Google platform. The results of the research that was developed for the dissertation were that, despite the non-quantitative expressiveness of propositions, the debates and repercussions of the theme in the social and educational environment resulted in significant impacts for the whole society that was already being polarized due to the speeches of hate constantly propagated. For school education, the impact took the form of the installation of a climate of fear and persecution against teachers, mainly those in the areas of human and social sciences.